NIRS monitoring of brain and spinal cord — detection of adverse intraoperative events. Issue 2 (2003) - Macnab Macnab, Andrew J. Andrew J.; Gagnon Gagnon, Roy E. Roy E.; Gagnon Gagnon, Faith A. Faith A.; LeBlanc LeBlanc, Jacques G. Jacques G.
Abstract : Near infrared spectroscopy (NIRS) monitors changes in oxygenated haemoglobin (HbO2 ), and redox status of cytochromeaa3 (cyt) continuously and non-invasively in living tissue. We present examples where clinically relevant changes in HbO2 and/or cyt were detected in real time, allowing intervention to avert potentially harmful hypoxic-ischaemic damage to the brain and/or spinal cord. Brain monitoring : In children undergoing surgery on cardiopulmonary bypass, observations include that: atrial fibrillation (cardiac arrhythmia) lowered cerebral HbO2 concentration; concealed haemorrhage decreased cerebral HbO2 concentration; inadequate level of anaesthetic resulted in spikes of changes in volume with interventions such as suturing; circulatory arrest reduced brain HbO2 and cyt redox status; and bypass pump problems compromised cerebral blood flow. Spinal cord monitoring : In the experimental animal, we observed that NIRS detected ischaemic change immediately following aortic compression, spinal column distraction (instrumentation to separate the vertebrae), and hypoxia. In an infant requiring release of a congenitally tethered spinal cord, we observed that traction on the spinal cord of the infant resulted in decreased total haemoglobin concentration. Summary : NIRS brain monitoring probably represents the "standard of care" during cardiac surgery because adverse events can be detected and quantified. Similarly, spinal cord monitoring could reduce ischaemic spinal cord damage in spinal cord surgery and aortic aneurysm repair.